I’dād al-Mawād al-Ta’līmiyyah li Mahārah al-Kalām ‘alā Asās al-Żakā’āt al-Muta’addidah bi al-Madrasah - Amir Mukminin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2021)
In learning to speak, teachers need teaching materials as tools/ media to help the success of the learning process so that students can master speaking skills. Success in the learning process sometimes fails to materialize due to a lack of student interest, because the material used is less attractive and does not match the type of intelligence/ potential of the student. Students have at least 8 types of intelligence but sometimes only a few are dominant. Students who tend to have certain intelligence will be more interested in carrying out learning activities according to their potential. So it is natural that it is still not successful because the teaching materials used do not contain material that is appropriate to the type of student intelligence. Objectives: 1). Describe the characteristics of teaching materials; 2) Knowing the feasibility of teaching materials; 3) Detecting the effectiveness of Arabic learning using teaching materials for learning multiple intelligences-based speaking skills. The method used is the research and development method. The validator of this case is an expert on the Arabic language and teaching material design. The subject of the field trial was 22 students. The data collection techniques are interviews, questionnaires, and tests. These conclusions are as follows: 1) The material contains educational books and CDs following the lessons learned. The validity of the material was prepared through three stages: reviews from language experts 94.1% with excellent scores, and experts in education and material design 84.1% with good scores. 2). The material specifications include the book title "Teaching Multiple Intelligences Speaking Skills". 3). The effectiveness of the material designed by the researcher has the effectiveness in improving the students' speaking ability. This can be seen in the pre-test and post-test results that the t-score calculated in this study (8.217) is greater than the t score at the 5% significance level.